IMPLEMENTATION OF THE CHILD-FRIENDLY CITY PROGRAM IN THE BASIC HEALTH SERVICES CLUSTER AT THE LIMA PULUH KOTA DISTRICT HEALTH CENTER, PEKANBARU - Natasya Amelia Putri; Ratna Dewi; Ainun Mardiah (Sultan Syarif Kasim State Islamic University, Riau, 2026)
This study aims to analyze the implementation of the Child-Friendly City Program in the primary health cluster at Lima Puluh Community Health Center, Pekanbaru City. This study uses George C. Edward III's policy implementation theory, which includes four main indicators: communication, resources, disposition, and bureaucratic structure. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Informants consisted of the Pekanbaru City Women's Empowerment and Child Protection Service, the person in charge of the community health center program, medical personnel, integrated health post cadres, and community service users. The results of the study indicate that the implementation of the Child-Friendly City Program at Lima Puluh Community Health Center has not been running optimally. From the communication aspect, the community health center has not received clear technical guidelines from Women's Empowerment and Child Protection Service. In terms of resources, child-friendly facilities such as playrooms and breastfeeding corners are available, but the number of medical personnel is still limited. The disposition of the implementers is considered good because the health workers demonstrate a friendly attitude towards children, while from the aspect of bureaucratic structure there is no specific SOP and a clear division of roles between the community health center and Women's Empowerment and Child Protection Service. Overall, the success of implementation is influenced by limited human resources, cross- agency coordination, and low community participation.